ISLAMIC ECONOMIC THOUGHT: A STUDY OF THE TAX SYSTEM AND FISCAL POLICY ACCORDING TO ABU UBAID - Anisa, Lina Nur (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This article analyzes Abu Ubaid's views on the tax system and fiscal policy in Islamic economics, with a focus on their relevance and application in the modern economic context. Through his work Kitab al-Amwal, Abu Ubaid emphasizes the importance of justice and the state's responsibility in wealth management, including taxes such as zakat, kharaj, and jizyah. The purpose of this study is to explore how these principles can be adapted to contemporary fiscal policy. The method used is library research, in which relevant primary and secondary literature is collected and descriptively analyzed to gain a comprehensive understanding of Abu Ubaid's perspective. The findings of this study show that Abu Ubaid's principles of justice and wealth distribution remain relevant in addressing economic inequality in the modern era. The implication is that Islamic economic principles, as proposed by Abu Ubaid, can be integrated into modern tax systems, particularly in Muslim-majority countries, to create a more just and inclusive fiscal system. Thus, Abu Ubaid's views offer a valuable alternative perspective for improving taxation systems and reducing social inequality.